Faktor-Faktor Peyebab Kesulitan Belajar Peserta Didik pada Mata Pelajaran Menggambar Teknik - Muhammad Rizki; R. Eka Murtinugraha; Rosmawita Saleh (Jurnal Pensil : Pendidikan Teknik Sipil, 2016)
This study aims to determine the factors that cause learning difficulties for subjects Technical Drawing experienced by students of class X Architecture Engineering Department of SMK Negeri 1 Jakarta Academic Year 2015/2016. Population are students of class X Architecture Engineering for 58 students. Data collection instrument used in this study using a questionnaire with four alternative answers have then analyzed by the method of factor analysis using software Excel 2010. Analysis test conducted on instrument reliability and validity, in which the results of the test are 26 items of 30 items declared valid by the results of reliability r11 = 0,899. Percentage results obtained by each of the factors that explain the overall study of the factors that cause learning difficulties for students physiological factors gets low category with 16%, whereas psychological factors are at sufficiently very low category with a value of 13% and environmental factors have a value of 71%, comprising 18% of the family environment, school environment 27% and 26% of the communities